2020
DOI: 10.3390/w12113256
|View full text |Cite
|
Sign up to set email alerts
|

Algicidal Activity of Cyperus rotundus Aqueous Extracts Reflected by Photosynthetic Efficiency and Cell Integrity of Harmful Algae Phaeocystis globosa

Abstract: Phaeocystis globosa is regarded as a notoriously harmful algal bloom species. Suppressing harmful algae using algicidal substances extracted from plants is considered an effective method. The physiological and biochemical processes of P. globosa were explored by exposure to different concentrations of aqueous extracts of Cyperus rotundus. All treatments indicated various inhibitory effects on the algal growth compared to the control samples without adding extracts. At 48 h, the 4, 8, and 16 mg/mL treatment gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…For example, phenolic acids 2-phenylphenol, p-hydroxybenzoic acid, protocatechuic acid, ellagic acid, gallic acid, p-coumaric acid and vanillic acid have effective allelopathic effects on the growth of harmful algae [48][49][50][51][52][53]. Additionally, some organic acids such as quinic acid, hexanedioic acid, linoleic acid, αlinoleic acid, palmitic acid and azelaic acid also exhibit strong allelopathic potential on controlling harmful algae [54][55][56][57][58]. However, Nakai et al found that quinic acid had no algal suppression effect [19].…”
Section: Discussionmentioning
confidence: 99%
“…For example, phenolic acids 2-phenylphenol, p-hydroxybenzoic acid, protocatechuic acid, ellagic acid, gallic acid, p-coumaric acid and vanillic acid have effective allelopathic effects on the growth of harmful algae [48][49][50][51][52][53]. Additionally, some organic acids such as quinic acid, hexanedioic acid, linoleic acid, αlinoleic acid, palmitic acid and azelaic acid also exhibit strong allelopathic potential on controlling harmful algae [54][55][56][57][58]. However, Nakai et al found that quinic acid had no algal suppression effect [19].…”
Section: Discussionmentioning
confidence: 99%